The Effect Of Family Support On Medication Adherence In Elderly Hypertensive Patients - Cahyaningrum, Efrida; Abidin, Zaenal; Marsanti, Avicena Sakufa (Health Science UDINUS, 2024)
Adherence to treatment in hypertensive patients is an important thing to note considering that hypertension is a disease that cannot be cured but can be controlled. Therefore, blood pressure needs to be checked regularly to prevent complications. Based on a preliminary study conducted in Cabean village, results were obtained from 20 respondents, 12 of whom were not compliant in undergoing treatment. This study is to determine the effect of family support on the level of adherence to treatment for people with hypertension in the elderly in Cabean Sawahan Village, Madiun. This type of research is a cross-sectional approach. The population in this study was hypertensive elderly patients as many as 123 people and the number of samples was 95 people. Data collection was conducted using the modified Morisky compliance scale questionnaire (mmas-8) and the Friedman, family support questionnaires. The data analysis used in this study was bivariate using the chi square test. The results of this study showed that there was an influence between family support p=0.017;PR 4,303;CI 95%(1,391-13,318)on the level of adherence to hypertension treatment in elderly patients. The conclusion of this study is that there is an influence between family support on the level of adherence to hypertension treatment in elderly patients.